Co-creation: a new approach to optimising research impact? - Jackson, C; Greenhalgh, P (Wiley, 2015)
Traditionally, academics benchmarked their success with metrics of publication such as journal impact factors or their personal h-index (a citation measure). Increasingly, researchers are required to demonstrate impact beyond academia